"CROSSFIT" AS A DIRECTION OF PHYSICAL TRAINING OF STUDENTS OF A PEDAGOGICAL UNIVERSITY - Botyaev V.L.; Dron A.Yu.; Dron Yu.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the possibilities and directions for the implementation of a modern fitness direction in a pedagogical university - crossfit. Methods and structure of the study. The first-year students of the faculty of physical culture and sports (n-21) and students of the non-sports faculty of a pedagogical university (n-27) took part in the pedagogical experiment. At the first stage, the attitude of students to crossfit, knowledge of the methodological and organizational forms of its implementation, as well as the desire of students to engage in this fitness area at a pedagogical university were determined. At the second stage, an entrance control and an assessment of the physical and functional readiness of students for crossfit classes were carried out. Results and conclusions. It is shown that the effectiveness of the implementation of the CrossFit direction in the extracurricular activities of students of a pedagogical university depends on the organizational and methodological support of both the classes themselves and the forms of control that allow using an individualized approach already in the first CrossFit classes. The authors propose a form of crossfit training in extracurricular activities of students of a pedagogical university, which has a high resource potential and the possibility of its implementation among young students.